(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Nowadays, the words “myth” and “mythology” are very frequent in ideological statements. It seems that the level of "mythology" of public life in our country has increased enormously lately, and we have stepped out of the realm of science and rationalism into some kind of "mythological" era.